A bio-based adhesive composed of polyelectrolyte complexes of lignosulfonate and cationic polyelectrolytes. (3rd May 2020) - Ushimaru, Kazunori; Morita, Tomotake; Fukuoka, Tokuma
Abstract: Polyelectrolyte complexes composed of lignosulfonate and cationic polyelectrolytes were used as bio-based adhesives. Sodium lignosulfonate (L-SO3 Na), a wood-derived anionic polyelectrolyte, was combined with three different cationic polyelectrolytes and the adhesive strength of the resulting complexes was evaluated on various substrates. Higher adhesive strength was observed with polar substrates (stainless steel, aluminum, and wood) compared to a nonpolar substrate (polypropylene). Complexes L-SO3 Na/poly(allylamine) and L-SO3 Na/ε-poly-l -lysine exhibited higher adhesive strength than the other polyelectrolyte complexes on aluminum and a commercial polyvinyl acetate adhesive on wood. In addition, our adhesives do not require any additional chemical reagents, such as organic solvents, crosslinkers, or condensation agents. The L-SO3 Na/ε-poly-l -lysine complex is a strong and completely biodegradable adhesive. This study demonstrates the use of lignosulfonate in the development of low-toxicity, sustainable, and biodegradable adhesives with excellent adhesive strength.